Light Color and the Commercial Broiler: Effect on Ocular Health and Visual Acuity - Remonato Franco, Bruna; Leis, Marina L.; Wong, Melody; Shynkaruk, Tory; Crowe, Trever; Fancher, Bryan; French, Nick; Gillingham, Scot; Schwean-Lardner, Karen (Frontiers in Physiology, 2022)
Light is a critical management factor for broiler production, and the wavelength spectrum, one of its components, can affect bird physiology, behavior and production. Among all the senses, sight is important to birds, and their visual system possesses several adaptations that allow them to perceive light differently from humans. Therefore, it is critical to consider whether exposure to monochromatic light colors influences broiler visual ability, which could affect behavioral expression. The present study examined the effects of various light colors on the visual systems of broiler chickens. Ross 708 males were raised from 0 to 35 days under three wavelength programs (blue (dominant wavelengths near 455 nm), green (dominant wavelengths near 510 nm) or white). Broilers were given a complete ophthalmic examination, including chromatic pupillary light reflex testing, rebound tonometry, anterior segment biomicroscopy and indirect ophthalmoscopy (n=36, day 21). To assess ocular anatomy, broilers were euthanized, eyes were weighed, and dimensions were taken (n=108, day 16 and day 24). An autorefractor was used to assess the refractive index and the corneal curvature (n=18, day 26). To evaluate spatial vision, broilers underwent a grating acuity test at one of three distances - 50, 75 or 100 cm (n=24, day 29). Data were analyzed as a one-way ANOVA using the MIXED procedure or Proc Par1way for non-normally distributed data. Significant differences were observed for refractive index and spatial vision. Birds raised under blue light were slightly more hyperopic, or far-sighted, than birds raised under white light (P=0.01). As for spatial vision, birds raised under blue light took less time to approach the stimulus at distances of 50 cm (P=0.03) and 75 cm (P=0.0006) and had a higher success rate (choosing the right feeder, P=0.03) at 100 cm than birds raised under white light. Improvements in spatial vision for birds exposed to blue light can partially explain the behavioral differences resulting from rearing broilers under different wavelengths.